SISTEM INFORMASI RANTAI PASOK PENETASAN D.O.C AYAM BOILER: (STUDI KASUS: GIRIWANGI JAYA FARM) - Siti Yuliyanti; Aep Saepudin; Rahmat Zaenal (LPPM STMIK BANDUNG, 2019)
Such technology has a rapid impact on the whole life, especially the provision of information for an organization / agency or company that requires a data management system that is fast, precise and accurate. To support the effectiveness of this thesis entitled,